2020
DOI: 10.3389/fneur.2020.563281
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Treatment Improves Intestinal Barrier Function After Spinal Cord Injury in Rats

Abstract: Intestinal barrier dysfunction is often observed clinically after spinal cord injury (SCI) and seriously affects long-term quality of life. Hyperbaric oxygen (HBO) treatment has been proved to promote barrier function recovery after injury, but the influence of HBO on intestinal barrier function following SCI is unclear. We aimed to investigate the effect and mechanisms of HBO treatment on intestinal barrier function by measuring the level of tight junction (TJ) proteins and the Ras homolog (Rho)/Rho-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Intestinal epithelial barrier dysfunction has proved after SCI (Liu et al, 2020(Liu et al, , 2021. The change leads to more opportunities for bacteria and their metabolites to enter the circulation, cause enterogenous infection, and further lead to the disorder of flora.…”
Section: Changes In Intestinal Epithelial Barrier Dysfunctionmentioning
confidence: 99%
“…Intestinal epithelial barrier dysfunction has proved after SCI (Liu et al, 2020(Liu et al, , 2021. The change leads to more opportunities for bacteria and their metabolites to enter the circulation, cause enterogenous infection, and further lead to the disorder of flora.…”
Section: Changes In Intestinal Epithelial Barrier Dysfunctionmentioning
confidence: 99%
“…The findings regarding parameters linked to vascular signaling and stress confirmed that HBO counteracts hypoxia by improving oxygen delivery to areas with diminished blood flow. HBO reduces oxidative stress by means of the upregulation of scavengers, SOD [ 28 , 29 , 30 ], and interferes with neutrophil adhesion to endothelia while enhancing cell-to-cell interaction at the level of tight- and gap junctions [ 31 , 32 ]. In case of impaired microcirculation, microvascular dynamics are improved by counteracting vasoconstriction, in part based on enhancement of the production of NO [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…They interact with the cytoskeleton, regulating smooth muscle tone, and regulating shape, migration and cell-to-cell adhesion. In particular, Rho-proteins influence the actin cytoskeleton, and thereby, smooth muscle tone regulation and seem to be important for modulating tight-junction protein function [ 58 , 59 ].…”
Section: Hyperbaric Oxygen and Regenerationmentioning
confidence: 99%
“…Following spinal cord injury intestinal mucosal injury score, intestinal permeability, and levels of Rho and ROCK1 were higher, whereas tight junction proteins were significantly lower than in controls. HBO downregulated the expression of Rho and ROCK1, whilst the expression of the junctional proteins Occludin and ZO-1 was elevated yielding decreased intestinal permeability while intestinal mucosal injury declined significantly [ 59 ].…”
Section: Hyperbaric Oxygen and Regenerationmentioning
confidence: 99%